Laparotomic vs laparoscopic ovariectomy: comparing the two methods. The ovariectomy in the bitch in laparoscopic era - Cassata, Giovanni; Palumbo, Vincenzo Davide; Cicero, Luca; Damiano, Giuseppe; Maenza, Antonio; Migliazzo, Aldo; Di Paola, Gioacchino; Vicari, Domenico; Fazzotta, Salvatore; Lo Monte, Attilio Ignazio (Acta Biomedica Atenei Parmensis, 2017)
Background and aim: The aim of the present work is to evaluate the effectiveness of the use of ultrasound scalpel during laparoscopic ovariectomy in the bitch. Methods: Two groups of 10 subjects each, of different races and ages, were compared. In the first group, ovariectomy was performed laparoscopically, using harmonic scalpel to remove ovary. In the second group surgery was performed by means of classical laparotomy. Results: Pre-operative time was similar in both groups. Total operative time, from incision to skin suture, showed significant difference between the two groups, being laparoscopy faster than laparotomy. Partial operative time for bilateral oophorectomy resulted lower using open technique, but, considering each ovary, there was no significant difference in both groups. Conclusions: The use of harmonic scalpel to perform ovariectomy during laparoscopy is an effective time-sparing surgical approach compared to the already great practicality of laparotomy.